Electron acceptor availability alters carbon and energy metabolism in a thermoacidophile. (16th August 2018) - Amenabar, Maximiliano J.; Colman, Daniel R.; Poudel, Saroj; Roden, Eric E.; Boyd, Eric S.
Summary: The thermoacidophilic Acidianus strain DS80 displays versatility in its energy metabolism and can grow autotrophically and heterotrophically with elemental sulfur (S°), ferric iron (Fe 3+ ) or oxygen (O2 ) as electron acceptors. Here, we show that autotrophic and heterotrophic growth with S° as the electron acceptor is obligately dependent on hydrogen (H2 ) as electron donor; organic substrates such as acetate can only serve as a carbon source. In contrast, organic substrates such as acetate can serve as electron donor and carbon source for Fe 3+ or O2 grown cells. During growth on S° or Fe 3+ with H2 as an electron donor, the amount of CO2 assimilated into biomass decreased when cultures were provided with acetate. The addition of CO2 to cultures decreased the amount of acetate mineralized and assimilated and increased cell production in H2 /Fe 3+ grown cells but had no effect on H2 /S° grown cells. In acetate/Fe 3+ grown cells, the presence of H2 decreased the amount of acetate mineralized as CO2 in cultures compared to those without H2 . These results indicate that electron acceptor availability constrains the variety of carbon sources used by this strain. Addition of H2 to cultures overcomes this limitation and alters heterotrophic metabolism.